IMPLEMENTATION OF NUMBERED HEADS TOGETHER (NHT) MODEL BASED ON AUDIO VISUAL MEDIA TO IMPROVE CONCEPTS COMPREHENSION OF COOPERATIVE - Arsitarasmi, Rokhmah Dwi; Sadiman, Sadiman; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2018)
The purpose of the research is to improve comprehension of the concept of cooperatives by applying Numbered Heads Together (NHT) model based on audio visual media in fourth grade students. The type of this research is classroom action research, it consists of two cycles. The subject of this research are the teacher and students in fourth grade of State Primary School Totosari No. 102 Surakarta at 2017/2018 academic year consist of 33 students. The data collecting technique using test, interview, observation, and documentation. The data validity techniques using content validity and triangulation of technique. The data analysis technique using Miles & Huberman interactive analysis model. The conclusions of the research are applying Numbered Heads Together (NHT) model based on audio visual media could improve comprehension of the concept of cooperatives.